Dataset for Identification of Homophobia and Transphobia for Telugu, Kannada, and Gujarati - Kumaresan P.K.; Ponnusamy R.; Sharma D.; Buitelaar P.; Chakravarthi B.R. (My University, 2025)
Users of social media platforms are negatively affected by the proliferation of hate or abusive content. There has been a rise in homophobic and transphobic content in recent years targeting LGBT+ individuals. The increasing levels of homophobia and transphobia online can make online platforms harmful and threatening for LGBT+ persons, potentially inhibiting equality, diversity, and inclusion. We are introducing a new dataset for three languages, namely Telugu, Kannada, and Gujarati. Additionally, we have created an expert-labeled dataset to automatically identify homophobic and transphobic content within comments collected from YouTube. We provided comprehensive annotation rules to educate annotators in this process. We collected approximately 10,000 comments from YouTube for all three languages. Marking the first dataset of these languages for this task, we also developed a baseline model with pre-trained transformers. © 2024 ELRA Language Resource Association: CC BY-NC 4.0.